2014
DOI: 10.1051/0004-6361/201424706
|View full text |Cite
|
Sign up to set email alerts
|

SARCS strong-lensing galaxy groups

Abstract: Aims.Various studies have shown a lensing bias in the mass-concentration relation of cluster-scale structures that is the result of an alignment of the major axis and the line of sight. In this paper, we aim to study this lensing bias through the mass-concentration relation of galaxy groups, thus extending observational constraints to dark matter haloes of mass ∼1013 −10 14 M . Methods. Our work is based on the stacked weak-lensing analysis of a sample of 80 strong-lensing galaxy groups. By combining several l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 125 publications
3
25
0
Order By: Relevance
“…The question of whether clusters are over-concentrated with respect to simulations has received considerable attention in recent years (e.g. Umetsu et al 2011;King & Mead 2011;Oguri et al 2012;Auger et al 2013;Foëx et al 2014;Umetsu et al 2014). Most of these works focus on strong lensing systems, which are expected to have higher projected concentrations than typical clusters of similar mass and redshift (Hennawi et al 2007;Oguri et al 2009Oguri et al , 2012.…”
Section: Mass-concentration Relationmentioning
confidence: 99%
“…The question of whether clusters are over-concentrated with respect to simulations has received considerable attention in recent years (e.g. Umetsu et al 2011;King & Mead 2011;Oguri et al 2012;Auger et al 2013;Foëx et al 2014;Umetsu et al 2014). Most of these works focus on strong lensing systems, which are expected to have higher projected concentrations than typical clusters of similar mass and redshift (Hennawi et al 2007;Oguri et al 2009Oguri et al , 2012.…”
Section: Mass-concentration Relationmentioning
confidence: 99%
“…Assuming a dark matter halo at z = 0.44 with M 200 ≈ 1 × 10 14 M ⊙ the concentration is c 200 ≈ 4.0 (computed with the procedures of Duffy et al 2008). SL2S J02140-0535 has also been studied by Foëx et al (2014), who were able to constrain the scale radius and the concentration parameters of galaxy groups using stacking techniques. SL2S J02140-0535, with an Einstein radius of ∼7 ′′ , belong to their stack "R3", which was characterized to have c 200 ∼ 10 and M 200 ∼ 10 14 M ⊙ .…”
Section: An Over-concentrated Galaxy Group?mentioning
confidence: 99%
“…Indeed, extensive studies of stronglensing events in field galaxies and relaxed galaxy groups have shown that in general light traces mass well within uncertainties in terms of the coincidence of centroids (Treu & Koopmans 2004;Koopmans et al 2006;Gavazzi et al 2007;Bolton et al 2008a;Dye et al 2008;Belokurov et al 2009;Limousin et al 2009;Suyu et al 2009;Jones et al 2010;Grillo & Christensen 2011;Brownstein et al 2012;Oguri et al 2012;Grillo et al 2013Grillo et al , 2014Sonnenfeld et al 2013;Foëx et al 2014;Newman et al 2015;Shu et al 2015). Furthermore, the smaller offsets in the more massive galaxy and opposite direction between offsets associated with individual lens galaxies in SDSS J1011+0143 cannot be properly explained without considering the relative motion of the two lens galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, approximately 100 group-scale strong lenses have been identified in the Cambridge And Sloan Survey Of Wide ARcs in the skY (CASSOWARY) Survey (Stark et al 2013), the Sloan Bright Arcs Survey (Kubo et al 2010), andthe Strong Lensing Legacy Survey-ARCS (SARCS) sample (More et al 2012), as well as other individual observations. No mass/light offsets have been reported in these group-scale lenses either, although some works explicitly fix the mass centroid to that of the light for systems with insufficient constraints (e.g., Dye et al 2008;Belokurov et al 2009;Limousin et al 2009;Suyu et al 2009;Jones et al 2010;Grillo & Christensen 2011;Oguri et al 2012;Grillo et al 2013Grillo et al , 2014Foëx et al 2014). Nevertheless, the nondetections suggest that these isolated lens galaxies and galaxy groups are substantially relaxed.…”
Section: Introductionmentioning
confidence: 99%